Can't Work or Won't Work: Quasi-Experimental Evidence on Work Search Requirements for Single Parents - Silvia Avram; Mike Brewer; Andrea Salvatori (Institute for the Study of Labor (IZA), 2016)
Increasing the labour market participation of single parents, whether to boost incomes or reduce welfare spending, is a major policy objectives in a number of countries. This paper presents causal evidence on the impact of work search requirements on single parents' transitions into work and onto other benefits. We use rich administrative data on all single parent welfare recipients, and apply a difference-in-differences approach that exploits the staggered roll-out of a reform in the UK that gradually decreased the age of the youngest child at which single parents lose the right to an unconditional cash benefit. Consistent with the predictions of a simple search model, the work search requirements have heterogeneous impacts, leading some single parents to move into work (especially those with strong previous labour market attachments), but leading some (especially those with weak previous labour market attachments) to move onto disability benefits (with no search conditionalities) or non-claimant unemployment.
Keywords: H53; I38; J64; 330; single parents; active labour market policy; work search conditionalities